Judicial creativity at the International Criminal Tribunals - Darcy, Shane; Powderly, Joseph (New York : Oxford University Press, 2010)
As the work of the International Criminal Tribunals for the Former Yugoslavia and Rwanda draws to a close, this collection appraises their impact. It particularly focuses on the position of judges as lawmakers within these tribunals, shedding light on the profound changes in international criminal law which these judges have instigated.
Sources of law and judicial interpretation -- Definition of crimes -- Forms of criminal liability -- Defences and fair trial rights -- Procedure.
Includes bibliographical references and index.
Keywords: International Tribunal for the Prosecution of Persons Responsible for Serious Violations of International Humanitarian Law Committed in the Territory of the Former Yugoslavia since 1991.; International Criminal Tribunal for Rwanda; International Criminal Tribunal for Rwanda; International Tribunal for the Prosecution of Persons Responsible for Serious Violations of International Humanitarian Law Committed in the Territory of the Former Yugoslavia since 1991.; International criminal courts; International crimes; Criminal procedure (International law); Judicial process; Judge-made law; Criminal jurisdiction; Criminal jurisdiction; Criminal procedure (International law); International crimes; International criminal courts; Judge-made law; Judicial process